2010
DOI: 10.3858/emm.2010.42.6.048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of CXC chemokine receptor 4 antagonist AMD3100 on bleomycin induced murine pulmonary fibrosis

Abstract: CXC chemokine receptor 4 (CXCR4), which binds the stromal cell-derived factor-1 (SDF-1), has been shown to play a critical role in mobilizing the bone marrow (BM)-derived stem cells and inflammatory cells. We studied the effects of AMD3100, CXCR4 antagonist, on a murine bleomycin-induced pulmonary fibrosis model. Treatment of mice with AMD3100 in bleomycin-treated mice resulted in the decrease of SDF-1 in bronchoalveolar lavage (BAL) fluids at an early stage and was followed by the decrease of fibrocytes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 52 publications
6
76
3
Order By: Relevance
“…Future experiments will seek to identify the specific interactions between Tregs and epithelial cells that govern overall CXCL12 expression and subsequent fibrocyte recruitment in the context of ALI. The reduction in lung collagen concentrations and fibrocytes in Rag-1 2/2 mice after CXCR4 receptor blockade with AMD3100 provides further evidence that the CXCL12-CXCR4 axis is critical in fibrocyte-mediated ALI fibroproliferation, and is consistent with previous studies that demonstrated a reduction in lung fibrosis in bleomycin models after CXCR4 or CXCL12 blockade (12,24). The lack of a significant difference in BAL cell count, protein, and lung CXCL12 concentrations between AMD3100-treated Rag-1 2/2 mice and PBS control mice, as well as the similar peak weight loss in each group, indicate that the difference in fibroproliferation did not result from reduced inflammation after LPS injury, and was instead attributable to the decrease in fibrocyte number.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Future experiments will seek to identify the specific interactions between Tregs and epithelial cells that govern overall CXCL12 expression and subsequent fibrocyte recruitment in the context of ALI. The reduction in lung collagen concentrations and fibrocytes in Rag-1 2/2 mice after CXCR4 receptor blockade with AMD3100 provides further evidence that the CXCL12-CXCR4 axis is critical in fibrocyte-mediated ALI fibroproliferation, and is consistent with previous studies that demonstrated a reduction in lung fibrosis in bleomycin models after CXCR4 or CXCL12 blockade (12,24). The lack of a significant difference in BAL cell count, protein, and lung CXCL12 concentrations between AMD3100-treated Rag-1 2/2 mice and PBS control mice, as well as the similar peak weight loss in each group, indicate that the difference in fibroproliferation did not result from reduced inflammation after LPS injury, and was instead attributable to the decrease in fibrocyte number.…”
Section: Discussionsupporting
confidence: 89%
“…AMD3100 is a nonpeptide antagonist of CXCR4 that inhibits the binding and function of CXCL12 with high affinity and specificity (23,24). Rag-1 2/2 mice received intratracheal LPS on Day 0, followed by daily intraperitoneal injections of either AMD3100 (200 mg in 250 ml) or sterile PBS (250 ml), starting on Day 0.…”
Section: Blockade Of the Cxcr4 Receptor With Amd3100 Decreased Fibropmentioning
confidence: 99%
“…One of the most important events in the early stages of epithelial repair is the migration of ATII cells to cover the denuded area, which is followed by later proliferation and differentiation. Bone marrow-derived hematopoietic stem cells also contribute to the repair of injured lungs, and these cells are recruited to the site of injury by chemokines such as CXCL12 (11,27,52,53,60). While the role of chemokine signaling is well recognized in the recruitment of stem cells and immune cells, the role of CXCL12/CXCR4 signaling in the migration of ATII cells has not been previously shown.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reporting on the recruitment of cultured MSCs in bleomycin-induced lung injury have supported opposing roles of these cells in terms of promoting fibrosis (Rojas et al, 2005;Song et al, 2010).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurymentioning
confidence: 92%